Tradução e adaptação transcultural do manual "Minimum standard of care — cross-cultural action guidelines for eating disorders" para o contexto brasileiro - Paiva, Ana Lúcia Boia Soares de (2023)
Eating disorders (ED) are characterized by persistent disturbance in eating or eatingrelated behavior that results in altered food intake or absorption and significantly compromises the physical health or psychosocial functioning of the individual. The growth of the prevalence of EDs in the general population and especially in the Brazilian population is recognized and patients present with comorbidities in about 90% of cases, generating significant losses in life quality of affected individuals, besides being one of the diseases with higher risk for suicide. Therefore, it is necessary to standardize the guidelines for the care and treatment of patients and their families or caregivers by health professionals who do not have access to specialized teams. On the other hand, it is justified to adapt a manual that is already validated and widely used internationally, since the process is less expensive than creating a new one and the use of an equivalent instrument facilitates communication and exchange of information within the scientific community. The objective of this work was to translate and cross-culturally adapt the manual ‘‘Minimum Standard of Care - Cross-Cultural Action Guidelines for Eating Disorders’’ to the Brazilian context, as authorized by the Academy for Eating Disorders that created it, then make it available with free access in the Brazilian version on the website of the Brazilian Association of Eating Disorders – ASTRAL BR. The method used in this work is scientific based and is anchored in a universalistic methodological approach, in other words, that understands culture as a significant impact factor for a given instrument when translated to have equivalence with the original version, reaching in this way its initial aim. Has considered five stages: Preparation, Translation, Synthesis of Translations, Back-Translation by sworn translators and a Committee Review of seven experts. As a result, the manual was translated and cross-culturally adapted for the Brazilian context and will be publicly available as a facilitating instrument, particularly for professionals who work with these public, providing access to safe and scientifically based information about these disorders and their specificities